2020
DOI: 10.1186/s12905-020-00920-y
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of endometrial sampling by vaginal tampons in women with Lynch syndrome

Abstract: Background: Endometrial sampling for the surveillance of women with Lynch syndrome is an invasive and painful procedure. The aim of this study was to evaluate the feasibility of a less invasive procedure of collecting vital cells by vaginal tampons. Methods: This was a prospective feasibility study of women scheduled to undergo annual gynecological surveillance, including endometrial sampling. We included consecutive asymptomatic women with Lynch syndrome or first-degree relatives and asked them to insert a va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Other alternative surveillance tools are also under investigation, including vaginal tampon‐based endometrial sampling, Pap test and urinary biomarkers for the detection of EC. Vaginal tampon‐based endometrial sampling is a noninvasive method that encourages patients to conduct home‐based self‐sampling, but its applicability and effectiveness need to be explored further 99 . A systematic review reported that the sensitivity of the Pap test was too low as a diagnosis method; however, advanced genetic and epigenetic technologies have provided a promising perspective 100 .…”
Section: Surveillancementioning
confidence: 99%
See 1 more Smart Citation
“…Other alternative surveillance tools are also under investigation, including vaginal tampon‐based endometrial sampling, Pap test and urinary biomarkers for the detection of EC. Vaginal tampon‐based endometrial sampling is a noninvasive method that encourages patients to conduct home‐based self‐sampling, but its applicability and effectiveness need to be explored further 99 . A systematic review reported that the sensitivity of the Pap test was too low as a diagnosis method; however, advanced genetic and epigenetic technologies have provided a promising perspective 100 .…”
Section: Surveillancementioning
confidence: 99%
“…Vaginal tampon-based endometrial sampling is a noninvasive method that encourages patients to conduct home-based self-sampling, but its applicability and effectiveness need to be explored further. 99 A systematic review reported that the sensitivity of the Pap test was too low as a diagnosis method; however, advanced genetic and epigenetic technologies have provided a promising perspective. 100 In addition, urinary biomarkers for EC detection based on cytology, metabolomics, spectroscopy, transcriptomics and proteomics have also shown potential clinical benefits.…”
Section: Surveillancementioning
confidence: 99%
“…While tampons can be left in the vagina for several hours to collect a representative sample, they are uncomfortable for postmenopausal women to use. 68 Urine is the perfect biofluid for non-invasive sampling because it is easy to collect, with the potential for large volumes, repeat samples or collection at pre-specified times of the day. It depends on urinary excretion of systemic cancer biomarkers, or the reliable contamination of urinary flow with uterine-shed tumour debris.…”
Section: Developing Novel Endometrial Cancer Detection Toolsmentioning
confidence: 99%
“…These collection tools lend themselves to self‐sampling, enabling women to collect their own biofluids at home for postal return to the laboratory. While tampons can be left in the vagina for several hours to collect a representative sample, they are uncomfortable for postmenopausal women to use 68 …”
Section: Developing Novel Endometrial Cancer Detection Toolsmentioning
confidence: 99%